Association between inflammation and cigarette smoking in cardiac remodeling after acute myocardial infarction - Cengiz Sabanoglu; Nilnur Eyerci; Orhan Karayigit; Mehmet Ali Felekoglu; Emrullah Kiziltunc; Omer Faruk Ates (Heart Vessels and Transplantation, 2022)
Objective: In this study, we aimed to investigate the relationship between smoking and adverse cardiac remodeling after ST-elevation MI (STEMI), and the association between smoking and inflammatory markers, including cytokine levels.